Cultivation of High-Value Vegetable sunder Solar Panels: A Pathway to Sustainable Income and Food Security - Sagar, Ram; Kumar, Rakesh; Singh, Samarpal; Rana, D K (Indian Horticulture, 2025)
The intersection of renewable energy and agriculture presents a promising opportunity to address both sustainable income generation and food security challenges. One such strategy is the cultivation of high-value vegetables under solar panels, known as agrivoltaics. Agrivoltaics involves the co-location of solar photovoltaic (PV) panels with agricultural crops, utilizing the same land for both energy generation and food production. By harnessing the synergy between renewable energy and agriculture, farmers can optimize land-use efficiency, increase farm profitability, and contribute to local food security.